2000
DOI: 10.3354/dao041083
|View full text |Cite
|
Sign up to set email alerts
|

Description of a presumptive hepatopancreatic reovirus, and a putative gill parvovirus, in the freshwater crayfish Cherax quadricarinatus

Abstract: The redclaw freshwater crayfish Cherax quadricarinatus has a reputation for being hardy and resistant to handling stress. However, in recent years, possibly since 1996, C. quadricarinatus farmers in northern Queensland have noted a decrease in stress resistance in their stock. A presumptive reovirus in the hepatopancreas, and a putative p a~o v i r u s in the gills, were associated with chronic mortalities in C. quadncarinatus at one northern Queensland farm. Hypertrophic nuclei with marginated chromatin were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
1
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 11 publications
1
30
1
1
Order By: Relevance
“…These were present in crayfish of all the experimental groups. In addition, 1 crayfish had a reo-like viral infection of the hepatopancreas (Edgerton et al 2000).The principal lesions seen in the viral injected crayfish were basophilic, INIBs in cells of the same tissues and tissue types described previously for the farm epizootic. In addition, the retinular, epicorneagenous and proximal cone cells of the eye were occasionally infected.…”
mentioning
confidence: 89%
“…These were present in crayfish of all the experimental groups. In addition, 1 crayfish had a reo-like viral infection of the hepatopancreas (Edgerton et al 2000).The principal lesions seen in the viral injected crayfish were basophilic, INIBs in cells of the same tissues and tissue types described previously for the farm epizootic. In addition, the retinular, epicorneagenous and proximal cone cells of the eye were occasionally infected.…”
mentioning
confidence: 89%
“…The affected crayfish had hypertrophic nuclei with rarefied chromatin but without CA intranuclear inclusion bodies in the gill epithelium which resembled histological changes consistent with a putative gill parvovirus reported by Edgerton et al (2000) in this species from northern Queensland. On this basis, it was assumed that these animals were infected with putative gill parvovirus.…”
Section: Discussionmentioning
confidence: 57%
“…However, genetic characterisation of the viruses has not been carried out and studies on immune-related genes of redclaw crayfish are sparse. Lesions characterised by hypertrophied nuclei with rarefied chromatin but without Cowdry type A (CA) intranuclear inclusion bodies that resemble those associated with putative parvovirus infection previously reported in C. quadricarinatus (Edgerton et al, 2000) were observed in a population, while these changes were not observed in another population of redclaw crayfish in the aquaculture facilities of the School of Veterinary and Biomedical Sciences, James Cook University. Therefore, this study was conducted to profile possible viral genomes and differentially expressed genes from gills of the two populations of crayfish using suppression subtractive hybridization (SSH).…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations